PENGARUH TEKNOLIOGI INFORMASI DAN KOMUNIKASI (TIK) TERHADAP KECERDASAN EMOSIONAL (EQ) PADA SISWA SMKN 1 SAMARINDA - ., Wasis Wiyono (MOTIVASI, 2013)
This study aims to determine the extent of the effect of Information and Communication Technology (ICT) on Emotional Quotient (EQ). Emotional Quotient in question is the sensitivity to recognize and manage their own and other people's feelings and sensitivity in managing these feelings then become the framework in behavior, socializing or taking the right decision. Emotional Quotient is divided into five main skills that will be investigated the effect of Information and Communication Technology in this study, namely: 1) Recognizing one's emotions; 2) Management emotion; 3) Motivate yourself; 4) Recognizing emotions in others; 5) Fostering relationships .The study was conducted in young children, especially student of vocational schools, 127 students study subjects, consisting of 33 students majoring in Multimedia class XI, 32 students majoring in Computer Technology and Networking class XI, 33 students majoring in Multimedia class XII, 29 students majoring Computer Technology and Networking class XII. Data analysis was performed with the statistical technique of Pearson product moment correlation, with the help of statistical program SPSS version 18 for windows.From the analysis of the research data obtained by the correlation effect of Information and Communication Technology (ICT) on Emotional Quotient at 0.433 with p of 0.000. This shows that there is a positive and highly significant between Information and Communication Technology with Emotional Quotient.